Landscape Design: Ten Important Things to Consider - Gail Hansen de Chapman (EDIS, 2009)
ENH-1112, a 10-page illustrated fact sheet by Gail Hansen de Chapman, guides homeowners’ step by step through the design process to develop a master plan for their environmentally sustainable residential landscapes. Includes references. Published by the UF Department of Environmental Horticulture, January 2009.